Djibouti : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2016)
This Selected Issues paper discusses the fiscal reforms needed for fiscal sustainability and inclusive growth in Djibouti. Djibouti is experiencing a predominantly debt-financed scaling up of public investment, which the authorities consider vital to boost growth and reduce widespread poverty and unemployment. Fiscal reforms will be needed to support fiscal consolidation and open up space for propoor expenditures that promote inclusive growth. Reform of the investment incentive framework and overall tax regime is also required to support fiscal consolidation and to level the playing field for investors and enhance revenue mobilization.